Eye gaze and L2 speakers' responses to recasts: A systematic replication study of McDonough, Crowther, Kielstra and Trofimovich (2015). (18th January 2020) - McDonough, Kim; Trofimovich, Pavel; Dao, Phung; Abashidze, Dato
Abstract : To confirm the role of social factors in mediating cognitive processes, this systematic replication study seeks to extend the generalizability of an exploratory study (McDonough, Crowther, Kielstra & Trofimovich 2015) that reported a positive association between eye gaze and second language (L2) speakers' responses to recasts. For this replication, L2 English speakers ( N = 74) carried out communicative tasks with research assistants who provided recasts in response to non-targetlike forms while both interlocutors' eye gaze behavior was tracked. Transcripts were analyzed for the occurrence of recasts in response to different error types, recast length, and L2 speaker responses. Eye gaze length for the research assistants (RAs) when producing the recast move and the L2 speaker when responding to the recast were obtained in seconds, and mutual gaze (i.e., simultaneous looking) was included as a binary eye gaze variable. A logistic regression model confirmed the findings of McDonough et al. (2015), with both L2 speaker and mutual eye gaze predictive of targetlike responses; however, the effect of L2 speaker's eye gaze duration was in the opposite direction as compared to the initial study. The implications are discussed in terms of understanding the role of eye gaze in face to face interaction.